Building Private Blockchain For Recording Student Values Data in Environment Faculty of Engineering at Universitas Muhammadiyah, Ponorogo - Aslan Alwi; Moh. Bhanu Setyawan; Munirah Munirah (IJAIT (International Journal of Applied Information Technology), 2021)
Storing student grades in universities is a sensitive issue when it comes to the security of campus computer networks. In this paper, we propose a blockchain model to ensure the secure storage of student grade data. Each record of recording student grades by a lecturer can be seen as a record in a journal or ledger. All records in one of the departments in a faculty can be seen as a student grade journal. Modeling this data by viewing data records as a journal allows us to model a database for all records in an encrypted and distributed manner. Namely, a model that resembles the blockchain model. In this perspective, a blockchain network can be made in which each node is stored in a different direction. So if there are three departments within the faculty, a blockchain with three vertices can be made. Each node keeps a copy of the overall student grade journal data. So that each node can mutually verify the validity of transaction records in each department. Student value journals are structured in such a way that they form a blockchain that builds hashes that lock together. This modeling of student value records answers the problem of being vulnerable to student scores hacked by irresponsible parties both from within the campus and from outside the campus. Security follows the protocols in the blockchain architecture.